Solitude in children and adolescents: A review of the research literature - Galanaki, Evangelia (Psychology and Education: An interdisciplinary Journal, 2013)
Although there is a substantial body of research on loneliness in children and adolescents, there is relatively less research evidence on solitude, as a state of being alone, and more specifically, on facets of solitude such as attitude toward aloneness, ability to be alone, and positive aloneness. In this paper, after some conceptual clarifications, research is reviewed on understanding the nature of solitude; affect of time alone; attitude toward aloneness; the links between solitude and adjustment; and the associations between solitude and other aloneness concepts. Finally, suggestions for future research on solitude in childhood and adolescence are offered.